Síntese e avaliação antioxidante e anticolinesterásica de derivados de Indois - Awad, Renata (2018)
Alzheimer's disease (AD) is a progressive and irreversible disorder considered the most common form of dementia in the elderly population. The main treatment line is based on the inhibition of acetylcholinesterase (AChE), which results in elevated levels of acetylcholine (ACh). In addition, oxidative stress caused by excess free radicals is a pathophysiological factor associated with AD. In recent years, there is a search for compounds that can serve as a prototype for the treatment of the disease, among them we can mention chalcones and their analogues. Indole derivatives, such as β-ketoindole, can be obtained from chalcones, as well as chalcones, have innumerable biological properties, such as antifungal, anti-inflammatory, antioxidant and anticholinesterase, being considered promising in the treatment of AD. The present work aims to evaluate the relationship between structure and activity of these compounds as potential antioxidants and anticholinesterases. Among the compounds synthesized, chalcones 18g, 18h, 18n and 18o and the indole 21f and 21n showed better antioxidant activities. In the antioxidant evaluation in analytical method by differential pulse voltammetry (DPV), all the chalcones had oxidation potential that could classify them with endogenous antioxidant potential, differently of the indole derivatives. In the test of the anticholinesterase activity performed with the 15 indole derivatives, all showed activity against both enzymes, acetylcholinesterase (AChE) and butyrylcholinesterase (BChE), with the exception of compounds 21f and 21i. A drug which is capable of inhibiting both enzymes may become preferable in the treatment of AD.